COMPARISON OF MARITAL SATISFACTION, FAMILY COHESION AND QUALITY OF LIFE AMONG WOMEN WITH AND WITHOUT CHRONIC PAIN - Azadeh Azadsarv, Firouzeh Sepehrianazar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Background & Aims: This study was done to compare the Marital Satisfaction, Family Cohesion and Quality of Life in Two Groups of Women with and without Chronic Pain. The research method was descriptive of causal-comparative. Materials & Methods: The population was consisted of all cancer patients and non-patients who were referred to specialist pain clinics in Rasht. The study sample consisted of was 30 Women with and 30 without Chronic Pain had selected via matching (homogenization) to a sampling available way. Data were collected by-Attachment styles questionnaire, marital satisfaction questionnaire, Sense of Coherence Scale and Quality of life questionnaire. Data were analyzed by using Multivariate analysis of variance (MANOVA). Results: The results showed that there was a significant difference in compare between Marital Satisfaction and Family Cohesion of Women with and without Chronic Pain (p<0/05) and, the difference in also was the significant difference between two groups in Quality of Life (p< 0/05). Conclusion: Based on the results, psychological variables should be considered for the treatment of chronic pain.